UHPLC-MS Phytochemical Profiling and Insight into Bioactivity of Rabelera holostea (Greater Stitchwort) Extract - Jelena S. Katanić Stanković; Jelena Đorović Jovanović; Danijela Mišić; Uroš Gašić; Stefanie Nikles; Zoran Marković; Rudolf Bauer (Molecules, 2023)
Rabelera holostea (L.) M. T. Sharples & E. A. Tripp (Greater Stitchwort), formerly known as Stellaria holostea L., is widespread in the warm temperate areas of Europe and Western Asia, the Caucasus region, as well as in some countries of North Africa. Nowadays it is considered as a weed, but earlier it was often used raw in salads or for the treatment of various inflammatory disorders. The goal of this study was to determine the constituents of the methanol extract of R. holostea aerial parts and its biological potential in terms of antioxidant, antimicrobial, and anti-inflammatory properties. Until now, the constituents and biological activities of this plant were not reported in detail. A comprehensive phytochemical profiling of the extract has shown that phenolic acids, such as ferulic, chlorogenic, and p-coumaric acid, flavonoids and flavonoid glucosides, such as chrysoeriol, rutin, and naringin, are the most abundant compounds. The antioxidant activity of R. holostea extract towards DPPH and ABTS radicals, but also the total antioxidant capacity and the inhibition of lipid peroxidation were moderate. The antimicrobial potential was pronounced mostly towards some fungi such as F. oxysporum (MIC 1.25 mg/mL), whereas the capacity of R. holostea to affect the growth of bacteria was much less pronounced. R. holostea extract was most inclined to anti-inflammatory activity. At a concentration of 50 µg/mL, it significantly inhibited both cyclooxygenase enzymes (COX-1 and COX-2) by 71.24% and 72.83%, respectively. Molecular docking studies indicated that chlorogenic acid and chrysoeriol are the main contributors to COX-1 and COX-2 inhibitory activity.